2019
DOI: 10.1089/cap.2019.0043
|View full text |Cite|
|
Sign up to set email alerts
|

New Formulations of Stimulants: An Update for Clinicians

Abstract: In the last 15 years, there has been a marked increase in the number of available stimulant formulations with the emphasis on long-acting formulations, and the introduction of several novel delivery systems such as orally dissolving tablets, chewable tablets, extended-release liquid formulations, transdermal patches, and novel ''beaded'' technology. All of these formulations involve changes to the pharmaceutical delivery systems of the two existing compounds most commonly employed to treat attention-deficit/hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 71 publications
0
34
0
Order By: Relevance
“…There is considerable variability in both the pharmacokinetics of stimulants across the day at an individual level, as well as in response [18,76,118,123]. Several factors potentially influence or contribute to the variability seen in individuals treated with stimulants, including drug specific factors (e.g.…”
Section: Variabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…There is considerable variability in both the pharmacokinetics of stimulants across the day at an individual level, as well as in response [18,76,118,123]. Several factors potentially influence or contribute to the variability seen in individuals treated with stimulants, including drug specific factors (e.g.…”
Section: Variabilitymentioning
confidence: 99%
“…Given the significant variability in the pharmacokinetics and response to stimulants, it can be concluded that there is no one treatment that is superior for all patients and underscores the importance of individualizing treatment by titrating the dose of each formulation for optimal effects in each patient while minimizing adverse events [18,76,118,123].…”
Section: Variabilitymentioning
confidence: 99%
See 3 more Smart Citations